Changes in vertical jump performance and body composition before and after COVID-19 lockdown - Tan, E.; Montalvo, S.; Gonzalez, M. P.; Dietze-Hermosa, M.; Min, S.; Dorgo, S. (Journal of Human Sport & Exercise, 2021)
This study aimed to determine the effects of a 16-week COVID-19 lockdown on body composition and vertical jump performance. Thirteen martial artists participated in this study. Participants were tested at: 1) pre-lockdown (pre), 2) post-lockdown (post), 3) two-weeks-post-lockdown (post+2), and 4) four-weeks-post-lockdown (post+4). Repeated-measures-ANOVAs were conducted with post-hoc analyses. Differences were observed in vertical jump height (VJH) (10.33%), peak velocity (PV) (3.10%), reactive-strength-index-modified (RSImod) (13.8%), and peak-propulsive-power (PPP) (6.00%) from pre-to-post. There as an increase from post-to-post+2 in VJ (13.06%), PV (4.12%), RSImod (14.0%), and PPP (4.66%). There was an increase from post to post+2 in VJH (10.8%), PV (3.1%), RSImod (14.0%), and PPP (3.0%). Fat mass (FM) and BF% increased from pre to post (13% and 11%, respectively) and decreased from post to post+4 (8% and 11%, respectively); fat-free mass (FFM) decreased from pre-to-post (11%) and decreased from post-to-post+4 (8%). There were moderate associations (rmc = 0.42-0.47) between FFM and VJH, FMM and PPP, FFM and PV, BF% and PV, and FM and PV. While the lockdown resulted in a significant decrease in vertical jump performance and increases in BF and FM, participant`s performance returned to pre-lockdown levels after only 2-4 weeks of post-lockdown training by decreasing BF, FM, and increasing FFM.